The social impact of distance learning in Roman schools: “Success,” social innovation, teaching practices - Lo Presti, Veronica (Frontiers in Sociology, 2023)
Faced with the national emergency linked to the spread of COVID-19 in Italy, digital technologies have made it possible to carry out the ordinary activities of the various educational agencies through the main tool of Distance Learning (DaD). The intensive use of information and communication technologies (ICT) and the guarantee of accessibility represent an enabling prerogative for current education systems, enriching training in a variety of ways and opportunities which must be accessible to all. ICTs take on a propulsive function for change in schools because they make it possible to affect the school setting, to transform the learning environment by redesigning space, reorganizing time, modifying communication and socialization processes, encouraging, in students, the development of key competencies in digital literacy and media education. Considering the context of a school transformed and renewed by the teaching and training potential of ICT, it becomes central to reconstruct the requests and needs developed by the practitioners of educational policies to cope with the reorganization of teaching methods and times at the time of DaD. Starting from these premises, the paper focuses attention on the social impact (Stern, 2016) of DaD to evaluate: the extent and intensity of the methodological-didactic innovation required of teachers for the organization and conducting remote lessons; the increase—in students—of transversal and digital literacy skills (team working, problem solving, etc.) potentially associated with the use of ICTs; the involvement and collaboration of families in the process of assessing and verifying learning. The reflection is part of a broader research project by the University of Sapienza University of Rome entitled “The social impact assessment of DaD after COVID-19”; a 3 year evaluation research addressed to a typological sample of upper secondary schools in Rome classified on the basis of the Infrastructure and Equipment indicator of the Rav and the social effect of the school (school effect) on the academic performance of students in the tests Invalsi. The evaluation aimed to identify—from the DaD experience—indications useful in re-designing the school's intervention strategy in the phases following the pandemic; for this reason it adopted an analysis perspective that valorized the positive and most successful aspects in the testimonies of the teachers and students involved in the first phase of the research (conducted in May–June 2021). Within the framework of the Positive Thinking Evaluation, the empirical evidence—collected through the administration/conduction of semi-structured interviews, focus groups, online ethnographic observation of the lessons in DaD—will allow us to reflect on some dimensions of success and of particular social innovation for the teachers' teaching practices and the students' learning processes in DaD. In the Positive Thinking Evaluation, success is a positive effect (not just a “good practice”), even an unexpected one, of an activity that has produced a positive change in the context of program implementation.